Lycium barbarum polysaccharide alleviates dextran sodium sulfate-induced inflammatory bowel disease by regulating M1/M2 macrophage polarization via the STAT1 and STAT6 pathways - Wang, Juan; Gao, Huiying; Xie, Yuan; Wang, Peng; Li, Yu; Zhao, Junli; Wang, Chunlin; Ma, Xin; Wang, Yuwen; Mao, Qinwen; Xia, Haibin (Frontiers in Pharmacology, 2023)
Disruption of colonic homeostasis caused by aberrant M1/M2 macrophage polarization contributes to the development of inflammatory bowel disease (IBD). Lycium barbarum polysaccharide (LBP) is the primary active constituent of traditional Chinese herbal Lycium barbarum L., which has been widely demonstrated to have important functions in regulating immune activity and anti-inflammatory. Thus, LBP may protect against IBD. To test this hypothesis, the DSS-induced colitis model was established in mice, then the mice were treated with LBP. The results indicated that LBP attenuated the weight loss, colon shortening, disease activity index (DAI), and histopathological scores of colon tissues in colitis mice, suggesting that LBP could protect against IBD. Besides, LBP decreased the number of M1 macrophages and the protein level of Nitric oxide synthase 2(NOS2) as a marker of M1 macrophages and enhanced the number of M2 macrophages and the protein level of Arginase 1(Arg-1) as a marker of M2 macrophages in colon tissues from mice with colitis, suggesting that LBP may protect against IBD by regulating macrophage polarization. Next, the mechanistic studies in RAW264.7 cells showed that LBP inhibited M1-like phenotype by inhibiting the phosphorylation of STAT1, and promoted M2-like phenotype by promoting the phosphorylation of STAT6. Finally, immunofluorescence double-staining results of colon tissues showed that LBP regulated STAT1 and STAT6 pathways in vivo. The results in the study demonstrated that LBP could protect against IBD by regulating macrophage polarization through the STAT1 and STAT6 pathways.